Komunikasi Organisasi Pemerintah Kabupaten Banyuwangi dalam Meningkatkan Pelayanan Publik (Universitas Negeri Surabaya, 2022)
The effectiveness of a government system is largely determined by the good and bad implementation of public services. The Banyuwangi Regency Government, which has mostly rural areas, has major challenges in improving services, including limited access and social restrictions due to the pandemic. This fact is the reason the Banyuwangi Regency Government created the Village Flower program. This research aims to find out how the organizational communication of the Banyuwangi Regency Government improves public services through Bunga Desa Program. Using a qualitative method with a case study approach, researchers hope to collect empirical and factual data on organizational communication applied by the Banyuwangi district government. The systems approach theory by Richard Farace is used to see the components, processes, and properties of the system in the Banyuwangi District Government in the Bunga Desa program that affect the improvement of public services in the village.